26.54-t=.5(50-t)

Simple and best practice solution for 26.54-t=.5(50-t) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 26.54-t=.5(50-t) equation:


Simplifying
26.54 + -1t = 0.5(50 + -1t)
26.54 + -1t = (50 * 0.5 + -1t * 0.5)
26.54 + -1t = (25 + -0.5t)

Solving
26.54 + -1t = 25 + -0.5t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '0.5t' to each side of the equation.
26.54 + -1t + 0.5t = 25 + -0.5t + 0.5t

Combine like terms: -1t + 0.5t = -0.5t
26.54 + -0.5t = 25 + -0.5t + 0.5t

Combine like terms: -0.5t + 0.5t = 0.0
26.54 + -0.5t = 25 + 0.0
26.54 + -0.5t = 25

Add '-26.54' to each side of the equation.
26.54 + -26.54 + -0.5t = 25 + -26.54

Combine like terms: 26.54 + -26.54 = 0.00
0.00 + -0.5t = 25 + -26.54
-0.5t = 25 + -26.54

Combine like terms: 25 + -26.54 = -1.54
-0.5t = -1.54

Divide each side by '-0.5'.
t = 3.08

Simplifying
t = 3.08

See similar equations:

| -3(2b+3)+(7b-4)=0 | | b-1+5b=36 | | -9=4+g | | 1.9q-4.4-2.1q=-1.2q-1.8 | | 5(3a+x)=ab-c | | (17-2x)(22-2x)=190 | | 8+(-6)= | | 3x^2+192=0 | | 2s^2-14s+24=0 | | 3(3r+1)-(r+4)=13 | | y^3-8= | | 25=9x+1-5x | | -2x+9=31 | | 5n-2(n-2)=-1 | | 7y=6(y+13) | | y-36=-25 | | 0.7x-0.8=-0.1x+3.2 | | 3(12.5)+18= | | 12=5-(x+4) | | 0.03x+0.08(100-x)=5.5 | | 2t^2-t-10=0 | | -0.2-(0.4x-0.3)=-1.8-0.6x | | 10c+5=3c+26 | | n+n+n+3=-20 | | 6(3y-3)+18= | | 67+12x=89 | | 17=3g+11-6 | | 8x+17=9x+7 | | 16y^2+32y+15=0 | | 3(4x-2)=2(6x-3) | | 3(8+6x)=12 | | x+2x+(1+5x)=25 |

Equations solver categories